Interpreting Currency Movements During the Crisis : What's the Role of Interest Rate Differentials? - Dowling, Thomas (IMF Working Papers; Working Paper ;, 2011)
Using an adaptation of the Uncovered Interest Parity (UIP) condition, this paper analyzes the drivers behind the large, symmetric exchange rate swings observed during the financial crisis of 2008-2010. Employing a Nelson-Siegel model, we estimate yield curves and decompose the exchange rate movements into changes we attribute to monetary policy and a residual. We find that the depreciation phase of the currencies in our sample was largely dominated by safe-haven effects rather than carry trade activity or other return considerations. For some countries, however, the appreciation that began at the end of 2008 seems largely to reflect downward movement in the cumulative revisions to nominal forward differentials, suggesting carry trade.